Effect of Interstock on Growth and Yield of Hevea Brasiliensis (Muell. Arg.) - Ahmad, Bastiah (1990)
This study explores the possibility of using interstock in vegetative propagation to improve the growth and yield of Hevea brasiliensis (m.e.l. Arg.). The parameters investigated were growth and yield of young and mature trees. Other parameters studied included leaf and stomatal characters, photosynthetic rate and bark anatomy of scion with the objective of providing possible explanations for some of the interstock effect on scion growth and yield. The various aspects of scion growth affected by inter stock clones were scion height, girt h and its increment, dry weights of various plan parts, mean relative growth rate and mean net assimilation rate, t he distribution of dry matter intovarious plant parts, leaf area, leaf area ratio, photosynthetic rate, stomatal frequency and stomatal size.